Solve for h h/6-1=3

Math
h6-1=3
Move all terms not containing h to the right side of the equation.
Tap for more steps…
Add 1 to both sides of the equation.
h6=3+1
Add 3 and 1.
h6=4
h6=4
Multiply both sides of the equation by 6.
6⋅h6=6⋅4
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 6.
Tap for more steps…
Cancel the common factor.
6⋅h6=6⋅4
Rewrite the expression.
h=6⋅4
h=6⋅4
Multiply 6 by 4.
h=24
h=24
Solve for h h/6-1=3

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top